Multiple imaging modality-guided radiofrequency ablation combined with transarterial chemoembolization for hepatocellular carcinoma in special locations - Yang, Bo-Shuai; Liu, Ling-Xiao; Yuan, Min; Hou, Yi-Bin; Li, Qing-Tao; Zhou, Su; Shi, Yu-Xin; Gao, Bu-Lang (Diagnostic and interventional radiology (Ankara, Turkey), 2020)
We aimed to evaluate the safety and effectiveness of radiofrequency ablation (RFA) combined with transarterial chemoembolization (TACE) guided by multiple imaging modalities for hepatocellular carcinomas (HCCs) in special (i.e., high-risk or unfavorable) locations compared with those in conventional locations. A total of 122 HCC patients were enrolled, including 85 patients (69.7%) with HCC in conventional locations and 37 (30.3%) with HCC in special locations. The clinical data, overall survival (OS), progression-free survival (PFS), and procedure-related adverse events were analyzed. RFA combined with TACE was successfully performed in all patients. Three complications (2.5%) occurred, with no significant difference between the conventional (n=1, 1.2%) and special (n=2, 5.4%) locations (P = 0.218). Complete tumor necrosis rate was not significantly different between the conventional (n=73, 85.9%) and special (n=34, 91.9%) locations at one-month imaging (P = 0.353). After a follow-up of 3-48 months, the PFS was 17 months for patients with HCC in conventional locations and 14 months for patients with HCC in special locations; one-year PFS rate was 68.1% in the conventional location group, not significantly (P = 0.741) different from 59.1% in the special location group. The OS was 28 months in the conventional location group while 32 months in the special location group. The cumulative one- and two-year OS rates were 89.9% and 63.3%, respectively, in the conventional location group, not significantly different from 96.3% and 65% in the special location group (P = 0.273). Age (P = 0.043) and tumor size (P < 0.001) were significant prognostic factors for OS, and tumor size (P < 0.001) was the only significant prognostic factor for PFS. RFA guided by multiple imaging modalities combined with TACE may be safe and effective for treating HCCs in special locations.